Innovación en envases alimentarios sostenibles: aprovechamiento de la cascara de cacao (Theobroma cacao L.) para el desarrollo de materiales biodegradables y ecológicos en el Ecuador - Moran Macias, Ingrid Marisol (2025)
The project aims to explore the potential of cocoa shells, an abundant by product of cocoa processing, to develop sustainable applications, in particular the production of biodegradable packaging at the industrial level. This commonly discarded waste contains compounds such as cellulose, hemicellulose and lignin, which make it suitable for the production of biomaterials. Its use not only boosts the bioeconomy by generating value added products, but also opens up new opportunities for economic development. The main objective is to valorize this by product, transforming it into a useful resource that contributes to reducing the environmental impact of conventional packaging. Interviews with farmers and studies conducted show a positive acceptance of these sustainable alternatives, which reinforces the project's potential to promote more environmentally friendly and resource efficient practices within the food industry. In addition, the use of cocoa shells for packaging offers an innovative alternative to single use plastic materials, whose environmental impact is of increasing concern. This technology can be implemented in cocoa growing areas, generating employment and strengthening the chain. It also aligns with global sustainability and circular economy objectives by transforming a waste product into a useful and environmentally friendly solution. In the long term, this initiative could serve as a replicable model for the use of other agroindustrial waste. Thus, it consolidates a proposal that not only seeks to reduce waste, but also to promote a more solid environmental awareness in production processes